The USAF characteristic K approach for cracks growing from small material discontinuities under combat aircraft and civil aircraft load spectra. (October 2017) - Huang, Pu; Peng, Daren; Jones, Rhys
Abstract: This paper investigates the ability of the USAF characteristic K approach to represent the growth of cracks from small naturally occurring material discontinuities. The examples discussed in this paper are associated with two different load spectra. The first case studied involves crack growth in AA7050-T7451 under a combat aircraft load spectrum. The second case studied the crack growth in AA7050-T7451 under a civil aircraft load spectrum. It is shown that using the root mean square value of ΔK in a load block to characterize the stress intensity factor together with the NASGRO equation, with the constants determined from constant amplitude tests on long cracks, enables the growth of small cracks under these two different complex load spectra to be reasonably accurately represented. Highlights: This paper reveals how the growth of small cracks from a hole can be captured. This paper reveals how the scatter in the cracks can be captured by small changes in the threshold term in the equation. This paper reveals how the USAF characteristic K approach can be used to capture the growth of small cracks.